Risk factors associated with wasting among children aged 6 to 24 months old in Gaza strip - Yassin, Maged; Taha, Mohanad; Abu Jamiea, Samar (International Journal of Medicine, 2016)
Wasting contributes to morbidity and mortality for children under 5 years of age particularly in the developing countries. This study identified the various risk factors associated with wasting among children aged 6 to 24 months old in Gaza Strip. The study sample consisted of 98 wasted children and 98 control children. A questionnaire interview was used. The World Health Organization Anthro software for assessing nutritional status of the world's children was applied. Data were computer analyzed using SPSS/PC statistical package version 21. Anthropometric data showed that birth weight was significantly lower in cases than controls (2.9±0.8 versus 3.1±0.6 kg, P=0.030). Weight and height were also significantly decreased in cases (P=0.000). Wasting was significantly higher among children of less educated mothers (χ2=8.110, P=0.044) and among children of less family income (OR=4.1, P=0.000). Children not received nutritional help or donation had more frequent wasting than those did (P=0.004). Wasting was significantly higher among non-exclusively breastfed children (OR=2.1, P=0.010) and among children who breastfed ≤12 months (P=0.021). Early introduction of complementary food increased wasting by 2.8 times (OR=2.8, P=0.001). Children with poor appetite had highest frequency of wasting (χ2=6.139, P=0.046). Wasting was significantly higher in respiratory and gastrointestinal tract infected children [OR=2.9, P=0.000 and OR=3.1, P=0.000, respectively). In conclusion, less income, not receive nutritional help or donation, non-exclusive breastfeeding and breastfeeding duration of ≤12 months, early start of complementary food and respiratory and gastrointestinal infections are the predicted risk factors of wasting among children in Gaza Strip.